Running for your life: A qualitative study of champion long-distance runners' strategies to sustain excellence in performance and health. Issue 8 (August 2020) - Bargoria, Victor; Timpka, Toomas; Jacobsson, Jenny; Halje, Karin; Andersson, Christer; Andersson, Gerhard; Bermon, Stéphane
Abstract: Objectives: To investigate champion long-distance runners' strategies for managing injury and illness symptoms and staying well. Design: Qualitative research study. Methods: Twelve long-distance runners were interviewed immediately after having competed in World Championships finals. Thematic analysis was used to categorise and structure the data. The results were presented as primary themes and overarching constructs representing connections between the primary themes. Results: The champion runners' basic tactic to manage symptoms of ill health was characterized by rapid adjustment of sports load and a strong incentive to learn from experience and professional advice. This tactic was named here educated flexibility. A secondary exigency tactic was associated with reaching short-term goals and a consequential acceptance of health hazards. The runners used economic and other environmental strain to explain use of the exigency tactic. Most champion runners' long-term strategy to stay well included both tactics successfully combined to maintain a performance level assuring a regular income. Avoidance of letting environmental strain and health problems create vicious circles was at the centre of these strategies. Conclusions: Champion runners' main strategy to stay well and sustain their superiority in performance was characterized by constantly paying attention to symptoms of ill health, listening to medical advice, and not letting environmental strain interfere with adjustment of sports load. Many top-level runners originate from global regions where formal education programs and health insurance plans are poorly regulated and supported. Bio-psychosocial models including empowerment at individual and systems levels should be considered when health services are planned for professional runners.